The Effectiveness of Sports Clinic: An Impact Study - Mortejo, Bpsu; C. Rivera, Kimberly; Nisay Jr., Romeo S. (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2022)
The purpose of the study. This study assessed the effectiveness of this Sports Clinic Program of the Bataan Peninsula State University at Brgy. Pto. Rivas Ibaba, Balanga City, Bataan as it investigated the level of the social impacts to the participants of the programs were determined. Materials and methods. The survey questionnaire was developed by the Sports Science Cluster of Bataan Peninsula State University and was validated by experts within the province. The result of the survey was analyzed through basic statistical treatment. Interviews were also conducted to the participant to further enhance the quantitative data gathered. Results. The result of the survey results that participant strongly agree that the BPSU Sports Clinic support their understanding the sport, it supports the athlete’s self-awareness on sport, BPSU Sports Clinic supports the athlete’s technical skills and the coaching staff have high commitment to athletes. Conclusions. Based on the interview conducted with the participants and stakeholders, there is a strongly agreement that the objectives set for this program were attained.